Pristimerin Suppresses RANKL-Induced Osteoclastogenesis and Ameliorates Ovariectomy-Induced Bone Loss - Qi, Dahu; Liu, Hui; Sun, Xuying; Luo, Danni; Zhu, Meipeng; Tao, Tenghui; Gao, Chenghao; Zhou, Chuankun; Zhou, Wei; Xiao, Jun (Frontiers in Pharmacology, 2021)
Osteoporosis is characterized by bone loss and destruction of trabecular architecture, which greatly increases the burden on the healthcare system. Excessive activation of osteoclasts is an important cause of osteoporosis, and suppression of osteoclastogenesis is helpful for the treatment of osteoporosis. Pristimerin, a natural compound, possesses numerous pharmacological effects via inactivating the NF-κB and MAPK pathways, which are closely related to osteoclastogenesis process. However, the relationship between Pristimerin and osteoclastogenesis requires further investigation. In this research, we examined the effect of Pristimerin on osteoclastogenesis and investigated the related mechanisms. Our results showed Pristimerin inhibited RANKL-induced osteoclast differentiation and osteoclastic bone resorption in vitro, with decreased expression of osteoclastogenesis-related markers including c-Fos, NFATc1, TRAP, Cathepsin K, and MMP-9 at both mRNA and protein levels. Furthermore, Pristimerin suppressed NF-κB and MAPK signaling pathways, reduced reactive oxygen species (ROS) production and activated the nuclear factor erythroid 2-related factor 2/heme oxygenase 1 (Nrf2/HO-1) signaling during osteoclastogenesis. Our in vivo experiments showed that Pristimerin remarkably ameliorated ovariectomy-induced bone loss, reduced serum levels of TNF-α, IL-1β, IL-6, and RANKL, and increased serum level of osteoprotegerin (OPG). Therefore, our research indicated that Pristimerin is a potential chemical for the treatment of osteoporosis.